Review on unmanned aerial vehicle covert communication network - Hengzhi BAI; Haichao WANG; Guoxin LI; Yuping GONG (Dianxin kexue)
Unmanned aerial vehicle (UAV) communication network is an important part of the future integrated space-aerial-ground network, and an effective support to achieve the global three-dimensional coverage of the communication network.The open characteristics of wireless channels make UAV communication vulnerable to malicious attacks by illegal users.Covert communication provides a promising solution for improving the security defense and privacy protection capabilities of UAV communication.However, the overlapping characteristics of the mobility of UAV systems and the requirements of covert communication scenarios bring severe challenges to the collaborative optimization of network resources.The UAV covert communication network was investigated from requirements, challenges, framework and main technologies perspectives.The architecture and model, performance characteristic, as well as potential candidate technologies were analyzed and discussed, in an attempt to outline the overall framework of UAV covert communication, and provide guidance for the subsequent research on UAV covert communication.